Developing Children's Creative Skills Through Community Service Program at TPA Majelis Ta'lim Al Ishlah South Jakarta - Budiman Tri Cahyadi; Anisul Fuad (UIN Siber Syekh Nurjati Cirebon, 2025)
Creative skills have an important role in creating critical thinking and problem-solving abilities. The method used in this service is Participatory Action Research (PAR), which involves the stages of problem identification, planning, implementation, and evaluation. This activity includes the application of the Iqro method to teach the Qur'an, as well as handicraft and hydroponic cultivation practices, which aim to increase children's creativity and innovation. The results of these activities show a significant improvement in Qur'anic comprehension and practical skills among participants, as well as increasing their enthusiasm in learning. It is hoped that this program can be a reference for the community and other majelis-ta'lim.